2018
DOI: 10.3389/fevo.2017.00174
|View full text |Cite
|
Sign up to set email alerts
|

Cultivable Bacterial Diversity in the Gut of the Chagas Disease Vector Triatoma dimidiata: Identification of Possible Bacterial Candidates for a Paratransgenesis Approach

Abstract: Since bacterial symbionts play a vital role in the metabolism of hematophagous insect vectors the method known as paratrangenesis, which consists of the use of cultivable insect symbionts to interfere with the transmission of vector-transmitted pathogens has been shown to be effective in certain vector control oriented studies. In Chagas disease research a recent study introduced transgenes through a parastransgenic approach and prevented the development of a vector species for this disease. However this appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Previous studies on triatomine microbiomes have suggested various factors, including ontogeny [48,51], species identity [41,47,50,51,108], sex [44,50], blood meal source [44], and T. cruzi infection [24,43,45,49,50], as determinants of microbiome composition, while another study claimed triatomine microbiomes have no determining factor [40]. Since many were based on limited sample size (e.g., N = 4 in [40], N = 14 in [44], N = 20 in [42], N = 9 in [41], N = 29 in [51]) and largely fragmented by host taxonomy, ontogeny, geographic origin, T. cruzi infection status, or were restricted to colony-reared bugs, it is difficult to draw comparative conclusions. We thus paid particular attention to our sampling design and molecular approach, ensuring that our study enabled multiple comparisons at different scales (i.e., different species from the same locality, different species from the same microhabitat, and different localities for the same species) across all ontogenetic stages.…”
Section: Consistency Of the Patterns: Biology Vs Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on triatomine microbiomes have suggested various factors, including ontogeny [48,51], species identity [41,47,50,51,108], sex [44,50], blood meal source [44], and T. cruzi infection [24,43,45,49,50], as determinants of microbiome composition, while another study claimed triatomine microbiomes have no determining factor [40]. Since many were based on limited sample size (e.g., N = 4 in [40], N = 14 in [44], N = 20 in [42], N = 9 in [41], N = 29 in [51]) and largely fragmented by host taxonomy, ontogeny, geographic origin, T. cruzi infection status, or were restricted to colony-reared bugs, it is difficult to draw comparative conclusions. We thus paid particular attention to our sampling design and molecular approach, ensuring that our study enabled multiple comparisons at different scales (i.e., different species from the same locality, different species from the same microhabitat, and different localities for the same species) across all ontogenetic stages.…”
Section: Consistency Of the Patterns: Biology Vs Methodologymentioning
confidence: 99%
“…In triatomines, thirteen high throughput sequencing studies published since 2015 have indicated a wide range of factors that potentially influence their microbiomes. However, it remains difficult to derive any consistent cross-species patterns since the studies utilised a wide variety of DNA templates, including pooled or individual bodies, entire abdomens, the distal part of the abdomen, whole guts, midguts, faeces, and cultured bacterial colonies [40][41][42][43][44][45][46][47][48][49][50][51][52], and were often further complicated by other variables (e.g., sex, locality, instar, T. cruzi infection status). Apart from these methodological differences, the disparity among studies could also reflect true biological characteristics of Triatominae.…”
Section: Introductionmentioning
confidence: 99%
“…Since many were based on limited sample size (e.g. N=4 in [33]; N=14 in [34]; N=20 in [37]; N=9 in [36]; N=29 in [42]) and largely fragmented by host taxonomy, ontogeny, geographic origin, T. cruzi infection status, restricted to colony-reared bugs, and employed different molecular methods, it is difficult to draw comparative conclusions. We thus paid particular attention to our sampling design and molecular approach, ensuring that our study enabled multiple comparisons at different scales (i.e.…”
Section: Consistency Of the Patterns: Biology Vs Methodologymentioning
confidence: 99%
“…Since 2015, twelve studies have investigated triatomine microbiomes using next-generation sequencing (NGS) tools. Unfortunately, the data lacks methodological consistency, having been retrieved from a wide variety of DNA templates, including pooled or individual bodies, entire abdomens, the distal part of the abdomen, whole guts, midguts, faeces, and cultured bacterial colonies [33][34][35][36][37][38][39][40][41][42][43][44], and often further complicated by other variables (e.g. sex, locality, instar, T. cruzi infection status).…”
Section: Introductionmentioning
confidence: 99%
“…Although previously reported in ticks [3 9, 93-95], the genus Brevibacterium is poorly known. Brevibacterium species occurring in haematophagous arthropods (kissing bugs, sand flies and horn flies) have been simply described as non-pathogenic bacteria with low abundance [96][97][98]. However, the recurrent presence of Brevibacterium in diverse unrelated haematophagous arthropods suggests that these bacteria may play a role in blood digestion by their arthropod hosts, and thus possibly in ticks.…”
Section: Discussionmentioning
confidence: 99%